(untitled) (Contemporary Journal of Social Science Review, 2025)
The current fast progress of artificial intelligence (AI) has reshaped the branding strategies, allowing them to be highly personalized to consumers. Personalization AI enables brands to process vast amounts of consumer data to create content, suggestions and experiences on a personalized basis, in real-time, transforming consumer brand relationships. The paper will discuss how AI-based personalization effects branding on consumer engagement and brand loyalty as quantitative. Applying relationship marketing theories, consumer engagement theories, and technology acceptance theories, the conceptualization of personalization as a strategic branding process in the context of improved emotional connection, perceived value, and trust is created. Based on survey data and statistical analysis, the study evaluates the effects of AI-driven personalization on cognitive, emotional, and behavioral engagement levels and the ensuing effects of engagement, which in turn leads to consumer loyalty. It is hoped that the findings will be used to add to the body of branding research by empirically confirming the need to use AI as an agent of sustainable consumer relationships. In practice, the research can provide the informational support to the marketers who want to find a balance between technological efficiency and human-oriented and ethical branding in a more data-driven market.